SIMULASI RANGKAIAN PENYEARAH SETENGAH GELOMBANG MENGGUNAKAN LIVEWIRE - Aryanti Aryanti; Clara Alcahya Palpa; Dimas Iqbal Fahrozy; M.Nabil Ar-Rassya; Nadya Aprilia (JURNAL TELISKA, 2025)
This study discusses the design and analysis of a half-wave rectifier circuit using the LiveWire Circuit application as a simulation medium. The main objective of this research is to understand the working principle of the diode as a rectifying component and to analyze the waveform and output characteristics produced through simulation. The circuit consists of an AC voltage source, a step-down transformer, a 1N4007 silicon diode, and a 1 kΩ load resistor. The simulation results show that the diode conducts current only during the positive half-cycle of the AC signal and blocks current flow during the negative half-cycle, thus producing a pulsating direct current (DC) output. The average DC voltage obtained from the simulation is 0.32 V, which is close to the theoretical value of 0.318 V, with a rectification efficiency of 40.6%. These findings demonstrate that the LiveWire application effectively represents circuit characteristics and provides real-time waveform visualization. The use of simulation through LiveWire not only enhances the understanding of basic electronics concepts but also offers a practical learning approach without requiring physical circuit assembly, making it an efficient educational tool for analyzing half-wave rectifier performance.